The Zebrafish as an Alternative Animal Model for Ecotoxicological Research and Testing - Braga, Ana Paula Andrade [UNESP]; Souza, Leticia Rosa de [UNESP]; Lima, Maria Gabriela Franco [UNESP]; Cruz, Jaqueline Matos [UNESP]; Souza, Ana Cristina Zullo de [UNESP]; Costa, Mariana Santos [UNESP]; Castro, Vera Lucia Scherholz Salgado de; Marin-Morales, Maria Aparecida [UNESP] (FapUNIFESP (SciELO), 2024)
Anthropogenic interventions have had a compromising effect on environmental health, intensifying the degradation of ecosystems, and the quantity of chemical pollutants released into nature. Therefore, research areas within the scope of environmental assessments and monitoring such as ecotoxicology have contributed to the determination of the toxic potential of contaminants. A small cyprinid known as the zebrafish (Danio rerio), the use of which has exponentially grown, is an alternative vertebrate model for scientific research, mainly in the assessment of environmental risks. The species exhibits several advantages for breeding in a laboratory, in addition to presenting multi-biomarkers of environmental toxicity. Thus, this review aims to present the main characteristics and advantages of working with this species, as well as show studies related to ecotoxicology involving biomarkers of toxicity in zebrafish. The results show a progressive trend towards employing the species in environmental risk analyses, it is an increasingly recommended species in the assessment of the toxicity level of a range of chemical pollutants. The development of future technologies must contribute to scientific advancement, rendering the potential application of this model organism an even more widespread one, which will certainly help in bridging knowledge gaps in various areas of study.
Keywords: Danio rerio; Ecotoxicology; environment pollution; model organism; toxicity biomarkers